1982
DOI: 10.1042/bj2070421
|View full text |Cite
|
Sign up to set email alerts
|

Mucolipidosis III β-N-acetyl-d-hexosaminidase A. Purification and properties

Abstract: Mucolipidosis III acid hydrolases possess an altered carbohydrate recognition marker needed for their lysosomal localization. As a result of this alteration, a portion of these enzymes is secreted from the cell to the extracellular spaces. The structural changes that may have occurred to one of these secreted enzymes, beta-N-acetyl-d-hexosaminidase A (EC 3.2.1.52) were investigated. Normal and mucolipidosis III urinary beta-N-acetyl-d-hexosaminidase A were purified to apparent homogeneity by using affinity [Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…213 lipidosis-II fibroblasts (for interpretation see Hasilik & von Figua, 1981). Our observations on the shift in the oligosaccharide pattern are consistent with a report on f,-hexosaminidase A (Kress et al, 1982), and contrast with another onf,-hexosaminidase B (Hirani et al, 1982), from mucolipidosis-III urine.…”
Section: Discussionsupporting
confidence: 93%
“…213 lipidosis-II fibroblasts (for interpretation see Hasilik & von Figua, 1981). Our observations on the shift in the oligosaccharide pattern are consistent with a report on f,-hexosaminidase A (Kress et al, 1982), and contrast with another onf,-hexosaminidase B (Hirani et al, 1982), from mucolipidosis-III urine.…”
Section: Discussionsupporting
confidence: 93%
“…Bi-and triantennary oligo saccharides comprising about 80% of the total oligosaccharides were found in human J3-glucocerebrosidase (58). It should be pointed out that this hydrolase is an example of a membrane-associated lysosomal enzyme (59 (64,(68)(69)(70)(71). This striking change results from a defect in these mutant cells in the phos phorylation of high-mannose oligosaccharides (see below).…”
Section: Common Modificationsmentioning
confidence: 98%
“…This may also be true for a-fucosidase [26]. Besides the precursor forms, mature forms of the B-hexosaminidase subunits are found in normal urine [24]. Miller et al therefore suggested [24] that P-hexosaminidase can be secreted into the urine via two pathways: a 'lysosomal' pathway leading to secretion of the mature form of the enzyme, and a 'nonlysosomal' pathway leading to direct secretion of the precursor form.…”
Section: Purifcation Of Lysosomal A-glucosidase From Human Urinementioning
confidence: 99%
“…The secretion of lysosomal enzymes is unrelated to that of the cytosolic enzyme lactate dehydrogenase, suggesting that the lysosomal enzymes found in the urine are not derived from exfoliated cells but are actively secreted. It has been shown by Miller and coworkers [24,25] that normal urine contains forms of B-hexosaminidase A and B with subunits of higher molecular mass than those present in placental and liver forms of the enzyme, and corresponding in size to those of the precursor forms of the subunits found in the culture medium of fibroblasts. This may also be true for a-fucosidase [26].…”
Section: Purifcation Of Lysosomal A-glucosidase From Human Urinementioning
confidence: 99%